The structure of coordination precursors as an effective tool for governing of size and morphology of ZnS and ZnO nanoparticles - Rafal Kruszynski; Marcin Swiatkowski (Journal of Saudi Chemical Society, 2018)
The zinc sulphide and zinc oxide micro- and nanoparticles of different shapes were synthesized from the five zinc coordination precursors, via controlled thermal decomposition process. The precursors were synthesized from zinc thiocyanate and N-donor ligands (2-aminopyrimidine, 1H-1,2,4-triazole and hexamethylenetetraamine), and they possessed different molecular and crystal structures (confirmed by X-ray crystallographic and spectroscopic studies). The proper set of parameters of precursors conversion process allows producing of ZnS in cubic (sphalerite) and hexagonal (wurtzite) form, as well as ZnO in hexagonal form. The relationship between the particles geometry (size and morphology) and the precursor structure, as well as the parameters of thermal conversion process was investigated. Keywords: Zinc thiocyanate, Coordination compound, Zinc sulphide, Zinc oxide, Crystal structure, Single precursor method